Sustainability Assessment in Housing Building Organizations for the Design of Strategies against Climate Change - Burciaga, Ulises Mercado (HighTech and innovation journal, 2020)
One of the biggest problems facing humanity is climate change, and the construction industry is one of the sectors causing the greatest impact. Therefore, design strategies accompanied by new methodologies are necessary. In this sense, this paper aims to assess sustainability for the design of organizational strategies against climate change, based on a holistic and systemic approach to sustainability development, in order to contribute to the decision-making in housing building organizations. The assessment was based on: 1) climate change indicators were selected from a case study; 2) a survey based on climate change indicators was designed and applied to 21% of the total organizations under study; and 3) critical indicators were identified. The result shows that 58% of the climate change indicators are critical and give evidence of the negative outlook that housing building organizations have in terms of sustainability. About 69% of these indicators belong to the cultural dimension. This demonstrates the lack of knowledge, customs, habits, and commitment to implementing sustainable strategies against climate change in these organizations. Finally, the results can contribute to designing strategies to promote sustainable building by the local government, and thus achieve more sustainable organizations that contribute to reducing their impact on climate change. Doi: 10.28991/HIJ-2020-01-04-01 Full Text: PDF